Eksplorasi Faktor Yang Memengaruhi Tingkat Kemiskinan - Yasjudan Dwirudhanto (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research explores the factors that play a role in determining the level of poverty in the Eastern region of Indonesia. Using qualitative and quantitative analysis approaches, this research tries to identify and analyze various social, economic, geographic and policy factors that contribute to poverty levels in the region. It is hoped that the findings from this research will provide deeper insight into the dynamics of poverty in Eastern Indonesia and assist in the formulation of more effective policies in efforts to reduce poverty.